Systematic review and meta-analysis of ocean acidification effects in Halimeda: Implications for algal carbonate production - Nadine Schubert; Lorenzo Alvarez-Filip; Laurie C. Hofmann (Climate Change Ecology, 2023)
Ocean acidification (OA) has been identified as one of the major climate-change related threats, mainly due to its significant impacts on marine calcifiers. Among those are the calcareous green algae of the genus Halimeda that are known to be major carbonate producers in shallow tropical and subtropical seas. Hence, any negative OA impacts on these organisms may translate into significant declines in regional and global carbonate production. In this study, we compiled the available information regarding Halimeda spp. responses to OA (experimental, in situ), with special focus on the calcification responses, one of the most studied response parameters in this group. Furthermore, among the compiled studies (n = 31), we selected those reporting quantitative data of OA effects on algal net calcification in an attempt to identify potential general patterns of species- and/or regional-specific OA responses and hence, impacts on carbonate production. While obtaining general patterns was largely hampered by the often scarce number of studies on individual species and/or regions, the currently available information indicates species-specific susceptibility to OA, seemingly unrelated to evolutionary lineages (and associated differences in morphology), that is often accompanied by differences in a species’ response across different regions. Thus, for projections of future declines in Halimeda-associated carbonate production, we used available regional reports of species-specific carbonate production in conjunction with experimental OA responses for the respective species and regions. Based on the available information, declines can be expected worldwide, though some regions harbouring more sensitive species might be more impacted than others.